IMPACT OF CONSERVATION TILLAGE ON ORGANIC MATTER DYNAMICS IN LOESS DRYLAND SOIL, PUNJAB, PAKISTAN - I. Naz; S. S. Ijaz; Mussie Y. Habteselassie; M. Ansar; K. S. Khan (Journal of Animal and Plant Sciences, 2022)
Conservation tillage and carbon sequestration are critical issues in rain-fed farming areas of Pakistan. Conservation tillage is not extensively used in developing countries on dryland soil where marginal farming is practiced. Therefore, primary purpose of this experiment was to determine the influence of conservation tillage practices on soil organic carbon (SOC), particulate organic matter (POC), mineral associated organic carbon (MOC), microbial biomass carbon (MBC) and dehydrogenase activity (Dha) in loess dry land Pothwar, Punjab, Pakistan. The tillage practices included zero tillage (ZT), minimum tillage (MT), reduced tillage (RT) and conventional tillage (CT) with mouldboardplough as a control in main plot and fallow-wheat (Triticumaestivum L.) and mungbean (Vigna radiate L.) crop rotation in sub plot as a split plot layout. The results indicated that ZT showed higher SOC (7.90 g kg-1), POC (2.35 g kg-1), MOC (5.1 g kg-1), MBC (359.37 μgg-1) and Dha (45.12 TPFμgg-1 dry weight) than CT. Among crop rotation, overall mungbean-wheat showed higher values as compared to fallow-wheat crop. The study indicated that conservation tillage practices with legume crop rotation have potential for improving soil organic carbon storage and hence carbon sequestration in soil.
Keywords: Conservation tillage; soil organic carbon; microbial biomass carbon; dehydrogenase enzyme; loess dryland; mungbean-wheat